การประเมินความต้องการจำเป็นของการจัดการระบบสารสนเทศในการบริหารวิชาการ ของโรงเรียนนวมินทราชินูทิศ เตรียมอุดมศึกษาน้อมเกล้า - เหมือนสนิท, จุฑากาญจน์; เก้าเอี้ยน, สุรศักดิ์ (An Online Journal of Education, 2018)
The objectives of this survey research were to study the needs assessment for academic management information system administration of Nawamintharachinutit Triamudomsuksanomklao School. The respondents were 104 school’s board and teachers. The data were collected using questionnaires of needs assessment for academic management information system administration of Nawamintharachinutit Triamudomsuksanomklao School. Quantitative data were analyzed using frequency, distribution, percentage mean and standard deviation while content analysis was used for qualitative data analysis. The research results showed that top five of needs assessment for curriculum management subject included 1) Data processing and analysis for curriculum development planning 2) Data processing and analysis for research development curriculum 3) Data collection for research development curriculum 4) Data collection for the involvement of those involved in curriculum development. 5) Data Collection for curriculum development. While the whole top five of needs assessment for instructional management included 1) Data processing and analysis for instructional planning 2) Data processing and analysis for instructional management in schools 3) Data processing and analysis for learning process 4) Data processing and analysis for teacher coaching and 5) Publishing and reporting results for classroom research accordingly.